Philosophy as frustration : happiness found and feigned from Greek antiquity to the present - Silver, Bruce S. (Studies in Moral Philosophy, 2013)
In Philosophy as Frustration: Happiness Found and Feigned from Greek Antiquity to Present Bruce Silver analyzes important views of happiness from Greek antiquity into the present. He argues that in many cases philosophers and positive psychologists do a poor job of defending the views of happiness they promote. Too often the philosophical approaches to what constitutes happiness are at odds with themselves and with possibilities for living happily. In some cases readers discover that the phrase "happy human being" is oxymoronic and that the most a person can expect is a life that is a measure of calm.